Pengelolaan Sumber Daya Alam dalam Perspektif Pembangunan Ekonomi Berkelanjutan: Penelitian - Bona Raja Purba; Titian Dhea Fresensia Purba; Sri Rosni Alfiat Laia; Flowremsari Haggata Ginting; Kevin Daniel Sirait (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the concept and practice of natural resource management (NRM) within the framework of sustainable economic development in Indonesia. Natural resources are vital for supporting economic activities and improving social welfare. However, excessive and unplanned exploitation has caused environmental degradation, social inequality, and a decline in ecosystem capacity. This research employs a descriptive qualitative method using a library research approach, focusing on conceptual and empirical analyses derived from literature, regulations, and reports from national and international institutions. The findings reveal that uncontrolled exploitation of natural resources provides short-term economic benefits but leads to significant social and environmental costs in the long run. Conversely, applying green economy principles, circular economy models, renewable energy adoption, and community participation can enhance resource efficiency and generate sustainable economic value. In the context of national development, integrating economic, social, and environmental policies is essential to achieve a balance between growth and sustainability. Strengthening environmental regulations, promoting eco-friendly technologies, and implementing the 3R principles (reduce, reuse, recycle) are crucial efforts to realize inclusive and environmentally responsible development for future generations.